2012
DOI: 10.1074/jbc.m111.330001
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Inhibitor of Growth 4 (ING4) Dimerization Domain Reveals Functional Organization of ING Family of Chromatin-binding Proteins

Abstract: Background:The tumor suppressor ING4 binds to chromatin with the H3K4me3 mark. Results: The structure of the ING4 dimerization domain was solved. Monomeric mutants did not enhance apoptosis in response to DNA damage. Conclusion: ING4 forms an antiparallel coiled coil, and dimerization is essential for apoptosis and growth inhibition. Significance: The structure and function of ING proteins are relevant for chromatin structure and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 49 publications
(43 reference statements)
0
24
0
Order By: Relevance
“…ING4 associates with p53 via its NLS region, leading to enhanced acetylation of p53 on Lys-382 and transcriptional activity of p53 [24,27]. ING4 dimerization through its N-terminal region is essential for apoptosis and growth inhibition [28]. In this study, we found that the NLS domain was also necessary for the binding of ING4 to AUF1 and the suppression of MYC translation and cell proliferation in p53-null K562 cells.…”
Section: Discussionmentioning
confidence: 58%
“…ING4 associates with p53 via its NLS region, leading to enhanced acetylation of p53 on Lys-382 and transcriptional activity of p53 [24,27]. ING4 dimerization through its N-terminal region is essential for apoptosis and growth inhibition [28]. In this study, we found that the NLS domain was also necessary for the binding of ING4 to AUF1 and the suppression of MYC translation and cell proliferation in p53-null K562 cells.…”
Section: Discussionmentioning
confidence: 58%
“…dimer: in green, the N-terminal coiled-coil domain responsible for the antiparallel dimerization; in blue, the PHD domain responsible for binding to the histone H3 tail; and in magenta, the connecting region containing the NLS. Below the scheme are the crystal structures of a dimer of the N-terminal domain [9] (PDB ID: 4AFL) and the PHD finger [7] (PDB ID: 2VNF). The NLS region was randomly built to connect the two domains and the positions of lysine and arginine residues are indicated by red spheres.…”
Section: Cloningmentioning
confidence: 99%
“…This modification is recognized by its conserved C-terminal plant homeodomain (PHD) with micromolar affinity [5][6][7]. The N-terminal region of ING4 is folded into a coiled-coil domain, forming an antiparallel dimer in solution and in living cells [8,9]. Therefore, ING4 can be described as an elongated dimer with two PHD fingers pointing to opposite directions and tethered by a disordered central region approximately 85 residues long ( Fig.…”
mentioning
confidence: 99%
“…Some PHD protein specifically recognizes tri-and di-methylated H3K4 (H3K4me3/2), with H3K4me3 as the preferred binding partner [100]. Others recognize unmodified histone residues such as H3R2 [101]. The ING (Inhibitor of Growth) family is one of the wellstudied tumor suppressors with PHD finger at its C-terminal [102].…”
Section: The Importance Of Chromatin Remodelingmentioning
confidence: 99%